Effects of Color and Size in Generating Intellectual Activity in Booth Spaces. Issue 3 (1st September 2017) - Baba, Teppei; Watanabe, Akiko
Abstract : This paper aims to clarify what kinds of design elements in environments stimulate mental activity. The study examined the effects on brain activity when wearable optical topography was worn in different booths having different sizes and color environments. The subjects′ mental activity in the prefrontal cortex was measured during working memory tasks conducted in four kinds of different booth: a small white booth, large white booth, small yellow booth, and large yellow booth. Physiological and psychological analyses revealed the following results. 1) The large yellow booth activated mental activity the most. 2) The booth size and color of the booth have an effect on the information processing activity of information processing. 3) The size of the booth has an influence on the physiological state. 4) Activation of brain activity has an effect on the affected reaction rate and percentage of correct answers.